Stock Rising: Stock Investment Simulation for the Smart Young Generation of Investing - Kholisa Dinuka, Vina; Aprayuda, Riyadi; Tiara; Wahana Wargadalam, Winanda; Fathurrahmi Lawita, Nadia (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to produce creative media for capital market financial literacy in the form of games as a simulation of investment and capital market practices for the younger generation, where the output of this study is expected to be a solution for the limitations of high/vocational school students who want to gain experience investing in the capital market but are hindered by the constraints of insufficient age and do not yet have an income. The method used in this study is research and development (R&D), which uses a 4D development model modified to four stages. It is defined, designed, developed, and evaluated. The research subjects of this study are students of Multi High School (MHS) Batam. The output or result of this study is a prototype of the Creative Media Financial Literacy Capital Market game and a guidebook for using capital market game simulations. The novelty of this study is producing new creative game media as a simulation of investment and capital market practices for the younger generation.